If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5w + 4(3 + w) = 66 5w + (3 * 4 + w * 4) = 66 5w + (12 + 4w) = 66 Reorder the terms: 12 + 5w + 4w = 66 Combine like terms: 5w + 4w = 9w 12 + 9w = 66 Solving 12 + 9w = 66 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 9w = 66 + -12 Combine like terms: 12 + -12 = 0 0 + 9w = 66 + -12 9w = 66 + -12 Combine like terms: 66 + -12 = 54 9w = 54 Divide each side by '9'. w = 6 Simplifying w = 6
| 11.3e-10.1e+7=13.24 | | 425/68=150/x | | 53a-79=26a+29 | | 106/4=x/12 | | =x^2+10x+9 | | 5x(-1)=10 | | X+1=5x-1 | | 53a-7.9=26a+29 | | 3/5(z-3)-11/5=-4 | | 7+2y=3.4 | | V/10.44-2.8=-4.422 | | X^2-9x^2+18=0 | | -5u+3(u+5)=29 | | Lnx^3/x^6 | | 14.63/9.315 | | 34z+63=-17z+471 | | 2/3(z-2)-11/3=-5 | | 5x+33=98 | | 10-10d=20 | | 2v=21 | | -80+-4x=120+6x | | (x+1)(x-1)=(x+1)(x-2) | | -80x+-4x=120+6x | | 3x-19=-70 | | 23-5=110 | | -(6y+1)-(-5y-8)=0 | | 3x^2-24x+28=0 | | 83overx=7 | | 3h-7=-7 | | -2(x-2)=-4x+14 | | -5-(-5/2) | | 33x-2+12x+2=180 |